THU0136 Major cardiovascular events in 434 rheumatoid arthritispatients treated with rituximab from a single-centre. (12th June 2018) - Giollo, A.; Gandrala, S.; Vojinovic, T.; Burska, A.; Md Yusof, M.Y.; Vital, E.M.; Hensor, E.M.A.; Buch, M.H.
Abstract : Background: Increased cardiovascular (CV) risk due to excess atherosclerosis in rheumatoid arthritis (RA) is attributed to systemic inflammation. Effective disease modifying drugs have been associated with reduced CV burden. Pre-clinical models of atherosclerosis suggest atheroprotective IgM and atherogenic IgG B-cell populations; with reduced atherosclerosis in murine models treated with depleting anti-CD20 monoclonal antibody suggesting relative preservation of protective B-cell population. The specific impact of rituximab (RTX) on the development of CV disease in RA has not been evaluated thus far. Objectives: To determine the incidence of major cardiovascular events (MACE) in RA patients treated with rituximab and factors associated with any increased risk. Methods: This was a single-centre, cohort study of patients with RA treated with ≥1 RTX cycle recruited prospectively. MACE outcomes were retrospectively identified as myocardial infarction, cerebrovascular accident, or death due to CV disease. Patients with and without MACE were compared for age, sex, CV risk factors (diabetes mellitus, hypertension, hyperlipidaemia, smoking, prior CV disease), disease characteristics (disease duration, ACPA, RF, methotrexate use, DAS28) and immunoglobulin levels. Association between the proportion of MACE and these variables of interest was analysed using the Student T test or Chi squared test as appropriate. Results: A total of 434 patients were studied (mean age 58 years [SD 13], 80% females). Total follow-up was 3211 patient-years (PY). Of these, 32/434 (7.4%) had a MACE (incidence rate 10 per 1000 PY). Forty-three deaths (any cause; 9.9%) were recorded, 6/43 and 26/391 deaths respectively in patients with and without MACE (14% vs 7%, p=0.114). Patients with MACE were older (64 [SD 9] vs 58 [SD 13] years, p=0.001), more likely to be diabetics (22% vs 6%, p=0.001), smokers (11% vs 5%, p=0.027), and were treated less frequently with methotrexate (4% vs 13%, por=0.002), but did not differ for hypertension, hyperlipidaemia, prior CV disease nor RA characteristics. Data on immunoglobulins at baseline and after the first cycle were available in the first instance in 287/434 patients. There were no significant differences in baseline immunoglobulin levels between patients with MACE and those without. However, the proportion of patients with MACE was significantly lower among those who had a reduction in their IgM levels from baseline (5% vs 21%, p=0.006), but not for IgG or IgA. No significant differences in the clinical profile of patients with decreased IgM and those without were observed. Conclusions: These preliminary data suggest decrease of IgM is associated with decreased risk of MACE in RA patients treated with RTX. Planned analysis on serial Ig with cumulative RTX exposure will clarify this initial observation. Whether and how any such association is related to a specific RTX-mediated effect and/or the overall reduction in the inflammatory burden deserves further investigation. Disclosure of Interest: None declared